ICT utilisation and its impact on the income of young fishermen in Malaysia - Bolong, Jusang; Omar, Siti Zobidah; Alby, Jeffrey Lawrence D'Silva; Mohamed Shaffril, Hayrol Azril; Abu Hassan, Musa (Universiti Putra Malaysia Press, 2013)
In order to meet the increasing demand for marine sources, superior offshore technologies have begun to be utilised. This study aims to discover the impact of ICT utilisation on the income of young fishermen. This is a quantitative study wherein a multi-stage random sampling approach was used to select a total of 121 registered fishermen as respondents. The data were collected using a pre-tested questionnaire. Mobile phones emerged as the most-used piece of ICT equipment among young fishermen, followed by GPS and echo sounders. Further analysis confirmed that usage of GPS and echo sounders is related to the income of young fishermen. Surprisingly, however, the study concluded that mobile phones – the most-used ICT device among young fishermen – have no significant association with the income of these young fishermen. This paper suggests a number of recommendations, and these can aid concerned parties to strategise more consistent methods to encourage young fishermen to use ICT.